Rash in Breast-Feeding Mother: Standardized Patient Case for Clerkship Students - Kelly Karpa; Katie Stollar (Association of American Medical Colleges, 2016)
Abstract Introduction Adverse drug reactions are a leading cause of morbidity and mortality. The full impact of these reactions is often not recognized by health care providers, which can lead to a cascade of additional medications prescribed to treat adverse effects caused by the inciting medication. Methods In this exercise, clerkship students are presented with a standardized patient portraying a medical problem. The students must identify the underlying cause of the problem, drawing on their knowledge of pharmacology, clinical therapeutics, special populations, and pharmacogenetics, to uncover and correct the deeper medical concerns, and compose a SOAP note. Thirty-five minutes were allotted for each student for this case. Results To date, this scenario has been used with all 23 third-year medical students at our regional campus. We found that most students tended to prematurely close the case after identifying the one obvious primary problem, leaving other issues unresolved. Discussion Utilizing this case with third-year medical students highlighted the need for continued reinforcement and application of pharmacologic principles throughout the clinical years of training. Furthermore, given that recent medical graduates often feel unprepared to prescribe safely and effectively, this case may also have utility as a teaching and discussion tool among medical residents. Additionally, it can be used in interprofessional educational activities with learners from pharmacy or nursing programs who will be involved in dispensing or administering medications to patients.